Activating mutations in the gene encoding the ATP-sensitive potassium-channel subunit Kir6.2 and permanent neonatal diabetes. - Gloyn, A; Pearson, E; Antcliff, J; Proks, P; Bruining, G; Slingerland, A; Howard, N; Srinivasan, S; Silva, J; Molnes, J; Edghill, E; Frayling, T; et al. (2004)
BACKGROUND: Patients with permanent neonatal diabetes usually present within the first three months of life and require insulin treatment. In most, the cause is unknown. Because ATP-sensitive potassium (K(ATP)) channels mediate glucose-stimulated insulin secretion from the pancreatic beta cells, we hypothesized that activating mutations in the gene encoding the Kir6.2 subunit of this channel (KCNJ11) cause neonatal diabetes. METHODS: We sequenced the KCNJ11 gene in 29 patients with permanent neonatal diabetes. The insulin secretory response to intravenous glucagon, glucose, and the sulfonylurea tolbutamide was assessed in patients who had mutations in the gene. RESULTS: Six novel, heterozygous missense mutations were identified in 10 of the 29 patients. In two patients the diabetes was familial, and in eight it arose from a spontaneous mutation. Their neonatal diabetes was characterized by ketoacidosis or marked hyperglycemia and was treated with insulin. Patients did not secrete insulin in response to glucose or glucagon but did secrete insulin in response to tolbutamide. Four of the patients also had severe developmental delay and muscle weakness; three of them also had epilepsy and mild dysmorphic features. When the most common mutation in Kir6.2 was coexpressed with sulfonylurea receptor 1 in Xenopus laevis oocytes, the ability of ATP to block mutant K(ATP) channels was greatly reduced. CONCLUSIONS: Heterozygous activating mutations in the gene encoding Kir6.2 cause permanent neonatal diabetes and may also be associated with developmental delay, muscle weakness, and epilepsy. Identification of the genetic cause of permanent neonatal diabetes may facilitate the treatment of this disease with sulfonylureas.